Comparative Analysis of Taper and Taperless Horizontal Turbine Blades at Labuhan Jukung Beach - Buana, Setiadi Wira; Prakoso, Yudhistira Alghifari; Kencana, Elsa Rizkiya; Yunesti, Putty; Wardani, Wulan Kusuma; Persada, Guna Bangun; Madi (Universitas Negeri Jakarta, 2025)
The uneven distribution of electricity demand across Indonesia necessitates the development of Renewable Energy Sources, particularly wind energy. This study evaluates the performance efficiency of horizontal-axis wind turbines equipped with two blade types: taper and taperless, both using the NACA 0012 airfoil. Aerodynamic simulations were conducted using QBlade software. Wind speed data from 2017 to 2022 were sourced from the European Centre for Medium-Range Weather Forecasts (ECMWF), while electricity consumption data were obtained from the Statistics Bureau of Pesisir Barat Regency. A quantitative approach using descriptive graphical analysis was employed to compare the performance metrics of the two blade designs. The results show that the taperless blade achieves higher power coefficient (Cp) and torque coefficient (Ct) values compared to the taper blade, although the taper blade produces greater torque (T). The energy conversion of the taperless blade reached 347.6 kWh, representing an increase of approximately 4.83% over the 331.6 kWh generated by the taper blade. Further analysis indicates that approximately 19 taperless-blade turbines are required to meet the daily electricity demand of 6,545 kWh in Pesisir Barat Regency. These findings support the recommendation to adopt taperless blades for improved wind energy utilization in the region.